The Effectiveness of Technology-Based Learning Methods on Literacy and Understanding of Fiction and Nonfiction Books Among Junior High School Students - Eka Ayu Amelia Putri; I Gede Ratnaya; Nyoman Trisna Herawati (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
This study aims to determine the effectiveness of the technology-based learning method in improving junior high school students’ literacy and comprehension of fiction and non-fiction books. The research employed a quantitative approach with a quasi-experimental design (Nonequivalent Control Group Design), involving two classes: an experimental class using the technology-based learning method and a control class using conventional teaching methods. The research instrument was a reading literacy test consisting of 25 multiple-choice questions. Data were analyzed using the Kolmogorov-Smirnov normality test, Levene’s test for homogeneity, independent-samples t-test, N-Gain calculation, and effect size measurement. The results showed a significant difference between the posttest scores of the experimental and control classes, with a significance value of 0.000 < 0.05. The average N-Gain score in the experimental class was 0.632 (moderate category) with an effectiveness level of 63.20%, while the control class scored 0.213 (low category). The effect size value of 1.255 was categorized as large, indicating a substantial influence of the technology-based learning method on improving students’ literacy and reading comprehension. These findings suggest that technology-based learning is worth implementing as an alternative instructional strategy to enhance students’ reading literacy in fiction and non-fiction materials.